Family psychology : theory, research, and practice - Thoburn, John W.; Sexton, Thomas L. (Praeger, 2016)
"Looking through the Systemic Lens "I can't go back to yesterday because I was a different person then" (Carroll, 2009). In the 1950s a systemic psychology developed from general system theory (von Bertalanffy, 1951), a new and revolutionary epistemology that directly competed with the Platonic and Aristotelian paradigms that had defined much of Western thought for centuries. Systems psychology developed as a reaction to the dominance of the Aristotelian based medical model of psychology represented by psychoanalysis, cognitive behavioral and humanistic psychologies. The medical model was characterized as individualistic (a focus on intrapsychic phenomena), dualistic (mind body split), reductionistic (reducing phenomena down to discrete categories) and radically objective (accepting only objective data as scientifically valid). The systemic model on the other hand, was characterized as relational (pathology and health are relationship oriented), holistic (the whole is greater than the sum of its parts), ecological (there is a reciprocal relationship between the biopsychosocial elements of being human) and subjective (the ideographic must be considered alongside the nomothetic)"--
Keywords: Family counseling; Family psychotherapy; Families : Psychological aspects; Family Therapy; perhetyö; perheterapia; psykoterapia; perheet; perheneuvonta; HEALTH & FITNESS : Diseases : General; MEDICAL : Clinical Medicine; MEDICAL : Diseases; MEDICAL : Evidence-Based Medicine; MEDICAL : Internal Medicine